The Impact of Individual Ethics on Reactions to Potentially Invasive HR Practices - Alder, G. Stoney (Journal of business ethics, 2007)
In recent years, the practices of work organizations have raised increasing concerns regarding individual privacy at work. It is clear that people expect and value privacy in their personal lives. However, the extent to which privacy perceptions influence individuals’ work attitudes is less clear. Research has explored the extent to which employee perceptions of privacy derive from characteristics of the programs themselves. However, there is a paucity of research that examines how the characteristics of the individual employee may influence perceptions of these programs. In this study we seek to shed light on this issue, as we examine how the individual ethical orientation of employees influences perceptions of a variety of human resource programs that have the potential to be perceived as invasive. Results indicate that ethical orientation exerts direct effects on perceived invasiveness of programs and exerts both direct and indirect effects on perceived appropriateness of programs. Implications for research and for managers adopting privacy-related programs are discussed.